The Optimization of Finishing Train Based on Improved Genetic Algorithm - Hongxia Liu; Xin Chen; Rongyu Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The central issue of finishing train is that we should distribute the thickness of each exit with reason and determine the rolling force and relative convexity. The optimization methods currently used are empirical distribution method and the load curve method, but they both have drawbacks. To solve those problems we established a mathematical model of the finishing train and introduced an improved Genetic Algorithm. In this algorithm we used real number encoding, selection operator of a roulette and elitist selection and then improved crossover and mutation operators. The results show that the model and algorithm is feasible and could ensure the optimal effect and convergence speed. The products meet the production requirements. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.3892